Integration of Content Marketing and Live Streaming of Purchase Intention through Online Customer Review as a Moderating Variable on Market place Users in West Java - Agustiana, Heppy (Terbuka Journal of Economics and Business, 2025)
This research is a quantitative study, namely the effect of independent variables, namely content marketing (X1) and live streaming (X2) on purchase intention (Y2) as the dependent variable and online customer review as a moderating variable (Y1). The population in this study were shopee marketplace users in West Java whose number was unknown using the Cochrun formula obtained a sample size of 322 respondents. Respondent samples have age criteria of more than 17 years who use the Marketplace application, have experience seeing firsthand the shopping offered by the Marketplace.  SmartPLS version 4 used to process and analyse  data collection result and its results are: 1 The Online Reviews variable  affected significantly by Content Marketing variable, 2 The Purchase Intention variable  affected significantly by Content Marketing variable, 3 the Online Reviews variable affected significantly by The Live Streaming variable, 4 Variable of Purchase Intention affected significantly by variable of Live Streaming, 5 The Online Review variable no effect on Purchase Intention, 6 Variable of Content Marketing affect to variable of Purchase Intention which mediated by the Online Reviews variable does not meet the requirements in this study, 7 Effect of Live Streaming variable to the variable of Purchase Intention mediated by the Online Reviews variable does not meet the requirements in this study